Beyond the Academic Journal: Unfreezing Misconceptions About Mental Illness and Gun Violence Through Knowledge Translation to Decision‐Makers. (31st March 2015) - Horwitz, Joshua; Grilley, Anna; Kennedy, Orla
Abstract : In a policy arena characterized by polarized debate, such as the consideration of legal interventions to prevent gun violence, research evidence is an important tool to inform decision‐making processes. However, unless the evidence is communicated to stakeholders who can influence policy decisions, the research will often remain an academic exercise with little practical impact. The Educational Fund to Stop Violence's process of "unfreezing" individual perceptions and conventional interpretations of the relationship between mental illness and gun violence, forming a consensus, and translating this knowledge to stakeholders through state discussion forums is one way to inform policy change. The recent passage of gun violence prevention legislation in California provides an example of successfully closing the knowledge translation gap between research and decision‐making processes. Copyright © 2015 John Wiley & Sons, Ltd.